2002
DOI: 10.1097/00007890-200207270-00005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of open, laparoscopic, and hand-assisted approaches to live-donor nephrectomy

Abstract: Minimally invasive donor nephrectomy is safe and effective for procuring normally functioning organs for live-donor transplantation. Of the two minimally invasive approaches examined, the hand-assisted technique was found to afford a number of important advantages, including facilitating teaching of residents and students, that it is more readily mastered by transplant surgeons, and that it may provide an additional margin of safety for the donor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 17 publications
3
70
0
3
Order By: Relevance
“…Many studies demonstrated an improvement of donor outcome by means of minimally invasive techniques [4][5][6][7]. Furthermore, there is evidence that endoscopic minimalinvasive kidney donation can increase the number of kidney donations because of shorter hospital stay, earlier return to work, good cosmetic outcome and better overall patient satisfaction [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies demonstrated an improvement of donor outcome by means of minimally invasive techniques [4][5][6][7]. Furthermore, there is evidence that endoscopic minimalinvasive kidney donation can increase the number of kidney donations because of shorter hospital stay, earlier return to work, good cosmetic outcome and better overall patient satisfaction [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of the LLDN include smaller wounds, less pain, earlier resumption of oral intake, and faster recuperation and earlier return to previous life style and to work. Nowadays, LLDN has been the surgery of choice for harvesting a kidney from a live donor (Kercher et al,2003;Troppmannet al, 2003;Tooher et al, 2004;Velidedeoglu et al, 2002).…”
Section: History Of Laparoscopic Live Donor Nephrectomymentioning
confidence: 99%
“…Evidences showed that the post-operative pain and quality of life of the donors, either operated by the hand assisted approach or the pure laparoscopic approach are similar, and both are significantly better that those of the traditional open approach (Velidedeoglu et al, 2002;Kercher et al, 2003;Troppmann et al, 2003;Mjøen et al, 2010;Leventhal et al, 2010). Laparoscopic LDN has evolved to be the surgery of choice for live kidney donors.…”
Section: Comments and Summary Of Laparoscopic Ldnmentioning
confidence: 99%
“…En nuestra opinión, está técnica puede tener sus indicaciones en determinadas cirugías que se prevean complicadas por el tamaño tumoral, la nefroureterectomía 19 , en la nefrectomía bilateral (decúbito supino) por enfermedad poliquística autosómica dominante 20 y en la nefrectomía del donante vivo [21][22][23] .…”
Section: Figura 12unclassified